Treasure Trade and Tradition : Post-Kidarite Coins of the Gangetic Plains and Punjab Foothills, 590-820 CE - Deyell, John S., (Brill | Manohar Publishers & Distributors, 2017)
This book has much to offer the numismatic enthusiast drawn to bold coinages shrouded in mystery. But it will also appeal to the general reader interested in a key formative period for the emergence of pre-modern India. It examines our turbulent social, religious, political and economic transition during the sixth through ninth centuries. The author focuses intensely on a single, tell-tale form of evidence, namely the enigmatic base gold dinara coins of the descendants of the Kidarite Huns. By thoroughly investigating the coins in their temporal, geographic and physical contexts, he teases out a fascinating story with three facets: treasure (gold and silver mineral wealth, as well as the spiritual wealth of pilgrimage centres sacred to Buddhism and Hinduism); trade (bearing horses, precious metals and pilgrims alike over the great caravan roads between Central Asia and north India); and tradition (the minting traditions of banking communities, the rulership traditions of royal lineages, and the spiritual traditions of religious art). Through its detailed analysis, the book clears up a great deal of confusion about the monetary systems of ancient Kashmir, the Punjab foothills and the Gangetic plains, from c. 590 to 820. With a large body of new metallurgical tests, the book defines, classifies and attributes this challenging series of trimetallic coins, revealing for the first time the money of Punjab's hill kingdoms nestled in the Siwalik valleys. Along the way, it prepares the groundwork for a new perspective on the role of hard money in early medieval economies, revealing preliminary evidence that the empire of the great Harshavardhana may have had a broadly-used coinage, contrary to expectations of the feudal model.